Design of a Solar Air Conditioning System Using Adsorption - Majd Muhannad Mohammad Hussain; Saleh Isam Mohammad Atieh (My University, 2019)
Air Conditioning systems is a very important part of human life. That is because of human comfort, equipment’s safety and...etc. But, the problem of these systems is the high consumption of energy. So, this project focused on renewable energy sources for air conditioning purposes. There are many examples of renewable energy sources. One of these examples is solar energy, it is a low cost and clean source of energy. This project will discuss the possibility of using solar energy in air conditioning systems by adsorption. Adsorption is chemical phenomena by mixing two types of materials, one of these materials is called adsorbent material and the other material called adsorbate material. This mixture can be used in cooling cycle by mixing these two types of materials and exposure of this mixture to heat energy by a solar collector. This project contains a collection of information’s about the chemical and physical properties of the adsorption technology to use it in a cooling cycle to make an acceptable cooling effect. This project discusses the ability of using the adsorption cooling cycle as an auxiliary system with a main air conditioning system. That is because of some constrains of the systems that used adsorption. These constrains have been discussed and clarified. One of these constrains is the availability of solar energy because it can be available all time. Another constrain is that the coefficient of performance of these systems has a maximum value of 0.53 and this the coefficient of performance can’t be used as a main air conditioning system. This project discusses the ability and working pairs of the adsorption cooling cycle like solar collector, adsorption tank, condenser and …etc. The description and all of the calculations of this cycle are will be explained in this project where the application and the analysis of these ideas are shown in this project. The project had been tested for two hours of heating cycle by heating the adsorption tank for two hours to initiate the adsorption process. Then, cooling cycle starts after the adsorption tank reaches 94.3⁰C. The cooling cycle had been tested for six hours. The test had been applied on a cup of water with volume of 1L. After the test finished, the coefficient of performance (COP) had been calculated. The calculations showed that the coefficient of performance reaches approximately to 0.2.